IN THE STUDY OF MEDICAL HELMINTHOLOGY, THE NEGATIVE CONSEQUENCES OF ASCARIASIS DISEASE ARE THE FREQUENCY OF OCCURRENCE AMONG THE POPULATION AND MEASURES to INTRODUCE PREVENTION METHODS INTO THE POPULATION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Currently, helminths are distinguished from common parasites found among people in almost all layers of the Earth's surface. Helminths have been causing several negative consequences in the body, mainly damaging the small intestine of the human body. Parasitised bat species are called "helminths". The science that studies helminths is helminthology and the diseases they cause are called helminthoses. Sexually mature parasitic flies, called helminths, parasitize mainly in vertebrates. Many of them parasitize endoparasites, that is, in various internal organs of the animal and human organism. Helminths are divided into biogelminths and geogelminths according to their development cycle. Intermediate or additional bosses are involved in the development cycle of biogelmints, as an example of biogelmints we can do with liverworm and example.